Public Debt Crisis in Spain and Europe Union. Cause or Consecuence? - López Prol, Javier (Papeles de Europa, 2014)
In this research it is analyzed through empirical evidence the orthodox thesis about excessive public expenditure, generator of public deficit and debt, as cause of the current crisis in the peripherical european countries. After looking at the tendency of these variables within the last decade in Spain and the European Union it concludes with some reflections about the aforesaid thesis.